Authorization for Posting Campaign Advertising
This document is a 1976 authorization form allowing the Jane Tolmach for Assembly committee to post campaign advertising on private property in the 36th Assembly District. The property owner grants permission, acknowledges they are not liable for damages or misrepresentation, and understands that all campaign materials will be removed within 10 days after the June 8, 1976 county election. The form includes spaces for the property location, authorized signature, and date, and lists campaign headquarters information and chairman Gerard Kapuscik.